Visualising the Landscape of Immersive Mobile Technologies in English Language Development: A Global Bibliometric Analysis (2020–2025) - Pek, Lim Seong; Mee, Rita Wong Mee; Yob, Fatin Syamilah Che; Ne’matullah, Khairul Firdaus; Miftah, M. Zaini; Derahvasht, Ali (International Journal of Interactive Mobile Technologies (iJIM), 2026)
Immersion technologies such as virtual reality (VR), augmented reality (AR), and game-based environments have emerged as a transformative approach to young learners’ English language development (ELD). This study maps global research on immersive English language development for young learners through a bibliometric analysis of 312 Scopus-indexed publications from 2020 to 2025. Using VOSviewer, co-citation and co-occurrence analyses identified key authors, institutions, journals, clusters, and research hotspots. The results indicate a significant increase in publications following the COVID-19 pandemic. Most research is produced in Asia, particularly in China, while contributions from Africa, Latin America, and the Middle East remain relatively limited. This indicates a significant imbalance in global research. Co-occurrence analysis highlights gaps between technological innovation and human-centered pedagogy, whereas co-citation analysis shows convergence between sociocultural theories and digital pedagogies. The study highlights the need for inclusive immersive learning ecosystems that support Sustainable Development Goal 4 on Quality Education. The paper concludes by suggesting directions for future research on immersive English learning for young learners, particularly in low-resource regions.